Double-Layered M2e-NA Protein Nanoparticle Immunization Induces Broad Cross-Protection Against Different Influenza Viruses in Mice - Wang, Ye (Adv Healthc Mater, 2019)
The development of a universal influenza vaccine is an ideal strategy to eliminate public health threats from influenza epidemics and pandemics. This ultimate goal is restricted by the low immunogenicity of conserved influenza epitopes. Layered protein nanoparticles composed of well-designed conserved influenza structures have shown improved immunogenicity with new physical and biochemical features. We generated structure-stabilized influenza matrix protein 2 ectodomain (M2e) and M2e-neuraminidase fusion (M2e-NA) recombinant proteins and produced M2e protein nanoparticles and double-layered M2e-NA protein nanoparticles by ethanol desolvation and chemical crosslinking. Immunizations with these protein nanoparticles induced immune protection against different viruses of homologous and heterosubtypic NA in mice. Double-layered M2e-NA protein nanoparticles induced higher levels of humoral and cellular responses compared with their comprising protein mixture or M2e nanoparticles. Strong cytotoxic T cell responses were induced in the layered M2e-NA protein nanoparticle groups. Antibody responses contributed to the heterosubtypic NA immune protection. The protective immunity was long-lasting. These results demonstrated that double-layered protein nanoparticles containing structure-stabilized M2e and NA can be developed into a universal influenza vaccine or a synergistic component of such vaccines. Layered protein nanoparticles can be a general vaccine platform for different pathogens.